2004
DOI: 10.1002/jcp.20218
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide specifically reduces the permeability of Cx37‐containing gap junctions to small molecules

Abstract: Gap junction intercellular communication (GJIC) plays a significant role in the vascular system. Regulation of GJIC is a dynamic process, with alterations in connexin (Cx) protein expression and post-translational modification as contributing mechanisms. We hypothesized that the endothelial autacoid nitric oxide (NO) would reduce dye coupling in human umbilical vein endothelial cells (HUVECs). In our subsequent experiments, we sought to isolate the specific Cx isoform(s) targeted by NO or NO-activated signalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
52
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 52 publications
(77 reference statements)
5
52
0
Order By: Relevance
“…A moderate (twofold) increase in NO prevented the effects of ADMA, whereas a fourfold increase in NO induced endothelial leakage. In agreement with our data, others have reported that small increases in NO promote intercellular junction formation in HUVECs (Kameritsch et al, 2005), whereas a substantial (three-to fourfold) increase causes endothelial leakage (Miyawaki-Shimizu et al, 2006), likely to result from a significant increase in nitration and nitrosylation of proteins (Predescu et al, 2005).…”
Section: Discussionsupporting
confidence: 93%
“…A moderate (twofold) increase in NO prevented the effects of ADMA, whereas a fourfold increase in NO induced endothelial leakage. In agreement with our data, others have reported that small increases in NO promote intercellular junction formation in HUVECs (Kameritsch et al, 2005), whereas a substantial (three-to fourfold) increase causes endothelial leakage (Miyawaki-Shimizu et al, 2006), likely to result from a significant increase in nitration and nitrosylation of proteins (Predescu et al, 2005).…”
Section: Discussionsupporting
confidence: 93%
“…27,28 Importantly, this NO influence depends on functional TGF, 27,28 suggesting neuronal NOS in macula densa cells as the source. Given the probable role of Cx40 in TGF signal transduction and the possibility of NO modulation of connexin conductance, 25,39 we postulated that the absence of Cx40 impacts on NO effects on the renal MR. This, however, was not the case, because inhibition of NO production has similar augmenting effects on the MR in wt, Cx40-ko, and Cx40KI45 mice.…”
Section: Discussionmentioning
confidence: 99%
“…NO is thought to modulate connexin conductance acutely 24 and expression chronically. 25 NO attenuates the magnitude of acute vasoconstriction elicited by receptor agonists such as Ang II and NE. 26 In addition, NO blunts the strength of the pressure-induced MR in RBF autoregulation, an effect specific to the kidney and dependent on JGA function and TGF.…”
mentioning
confidence: 99%
“…Gap junctional permeability can be regulated by small ions, such as Ca ϩϩ and H ϩ , 3 phosphorylation, 4,5 and possibly NO. 6,7 Connexin isoforms manifest molecular charge, size, and solute selectivity, 8 -10 and the translation of molecular selectivity into function can be inferred from the fact that deletion of one of the connexin isoforms can result in a unique phenotype that cannot be rescued by insertion or "knock in" of another connexin isoform (eg, see . Hemichannels forming the gap junctions can be composed of mixtures of proteins that vary according to location within the cell.…”
Section: Structure and Regulation Of Gap Junctionsmentioning
confidence: 99%